2003
DOI: 10.1179/016164103771953899
|View full text |Cite
|
Sign up to set email alerts
|

Mapping individual brains to guide restorative therapy after stroke: Rationale and pilot studies

Abstract: Some treatments under development to improve motor outcome after stroke require information about organization of individual subject's brain. The current study aimed to characterize normal inter-subject differences in localization of motor functions, and to consider these findings in relation to a potential treatment of motor deficits after stroke. Functional MRI (fMRI) scanning in 14 subjects examined right index finger tapping, shoulder rotation, or facial movement. The largest activation cluster in left sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 21 publications
0
21
1
Order By: Relevance
“…5 The range was similar to the range in healthy controls 6 and approximated electrode size. These data emphasize the anatomical variability in human motor system functional organization.…”
Section: Discussionmentioning
confidence: 65%
“…5 The range was similar to the range in healthy controls 6 and approximated electrode size. These data emphasize the anatomical variability in human motor system functional organization.…”
Section: Discussionmentioning
confidence: 65%
“…Accurate and detailed somatotopic mapping of the human body surface will improve basic understanding of the somatosensory system, guide neurosurgical planning, and assess plasticity and recovery after brain damage or body injuries (Borsook et al, 1998;Corbetta et al, 2002;Cramer et al, , 2003Cramer and Bastings, 2000;Cramer and Crafton, 2006;Lee et al, 1998Lee et al, , 1999Moore et al, 2000b;Ramachandran, 2005;Ramachandran and Rogers-Ramachandran, 2000;Rijntjes et al, 1997). Studies using fMRI have revealed somatotopic representations of the hand, fingers, wrist, elbow, shoulder, foot, toes, lips, and tongue in human brains (Alkadhi et al, 2002;Beisteiner et al, 2001;Blankenburg et al, 2003;Dechent and Frahm, 2003;Francis et al, 2000;Gelnar et al, 1998;Golaszewski et al, 2006;Hanakawa et al, 2005;Hlustik et al, 2001;Kurth et al, 2000;Lotze et al, 2000;McGlone et al, 2002;Miyamoto et al, 2006;Moore et al, 2000a;Overduin and Servos, 2004;Ruben et al, 2001;Servos et al, 1998;Stippich et al, 1999Stippich et al, , 2004van Westen et al, 2004; also see reviews in Burton, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that cross-sectional studies of motor recovery, even those with the most homogeneous of patient populations, may be subject to high variability in measurements of cortical activity across the population. In fact, one pilot study demonstrated, using a finger movement task, that centers of activation show considerable spatial variation across subjects and concluded that studies aimed at investigating hand representations in the post-stroke motor system may need to investigate individuals, rather than relying on population averages [18].…”
Section: Motor Recoverymentioning
confidence: 99%